Sexual Scripts and Criminal Statutes: Gender Restrictions, Spousal Allowances, and Victim Accountability After Rape Law Reform. (March 2018) - Levine, Ethan Czuy
The author provides a mixed-methods assessment of U.S. rape statutes to assess progress in reform. Contemporary statutes offer restrictive frameworks for distinguishing criminal from noncriminal sexual violence, many of which are grounded in gendered and heterosexist assumptions. Fourteen states retain gender restrictions in rape statutes. Twenty maintain marital distinctions that limit accountability for spousal rape. Furthermore, whereas explicit resistance requirements have been eliminated nationwide, implicit resistance expectations manifest through emphasis on physical force and involuntary intoxication. Analyses conclude with recommendations for further legal reform and a discussion of the potential for legislation to affect broader social perceptions of rape.